The Objective Structured Clinical Examination (OSCE): AMEE Guide No. 81. Part I: An historical and theoretical perspective. (2013) - Khan, Kamran Z.; Ramachandran, Sankaranarayanan; Gaunt, Kathryn; Pushkar, Piyush
Abstract : The Objective Structured Clinical Examination (OSCE) was first described by Harden in 1975 as an alternative to the existing methods of assessing clinical performance (Harden et al. 1975). The OSCE was designed to improve the validity and reliability of assessment of performance, which was previously assessed using the long case and short case examinations. Since then the use of the OSCE has become widespread within both undergraduate and postgraduate clinical education. We recognise that the introduction of the OSCE into an existing assessment programme is a challenging process requiring a considerable amount of theoretical and practical knowledge. The two parts of this Guide are designed to assist all those who intend implementing the OSCE into their assessment systems. Part I addresses the theoretical aspects of the OSCE, exploring its historical development, its place within the range of assessment tools and its core applications. Part II offers more practical information on the process of implementing an OSCE, including guidance on developing OSCE stations, choosing scoring rubrics, training examiners and standardised patients and managing quality assurance processes. Together we hope these two parts will act as a useful resource both for those choosing to implement the OSCE for the first time and also those wishing to quality assure their existing OSCE programme.